Answer:
see explanation
Step-by-step explanation:
The n th term ( explicit formula ) of an arithmetic sequence is
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Given a₁₂ = - 95 and a₃₇ = - 270 , then
a₁ + 11d = - 95 → (1)
a₁ + 36d = - 270 → (2)
Subtract (1) from (2) term by term to eliminate a₁
25d = - 175 ( divide both sides by 25 )
d = - 7
Substitute d = - 7 into (1) and solve for a₁
a₁ + 11(- 7) = - 95
a₁ - 77 = - 95 ( add 77 to both sides )
a₁ = - 18 , thus
= - 18 - 7(n - 1) = - 18 - 7n + 7 = - 7n - 11
= - 7n - 11 ← explicit formula
--------------------------------------------------------------
The recursive formula allows a term in the sequence to be found by adding the common difference d to the previous term, thus
=
- 7 with a₁ = - 18 ← recursive formula
Answer:
8x-10
Step-by-step explanation:
2x3x=6x, 2 x x=2x, 2x-5=-10 so 6x+2x-10= 8x-10
Answer:
I’m not sure m a
Step-by-step explanation: